2020
DOI: 10.1177/0301006620912134
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Perceptual Grouping Under Conditions of Inattention and Divided Attention

Abstract: Grouping local elements of the visual environment together is crucial for meaningful perception. While our attentional system facilitates perception, it is limited in that we are unaware of some aspects of our environment that can still influence how we experience it. In this study, the neural mechanisms underlying the Ponzo illusion were examined under inattention and divided-attention conditions using functional magnetic resonance imaging to investigate the brain regions responsible for accessing visual stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Previous studies repeatedly showed increased activity in parts of the parietal cortex (especially IPS and supramarginal gyrus) and a decrease in early visual areas (V1, V2) when participants perceived ambiguous stimuli as a grouped illusory Gestalt rather than an array of single elements (Carther-Krone et al, 2020;De-Wit et al, 2012;Fang et al, 2008;Grassi et al, 2016;Murray et al, 2002;Zaretskaya et al, 2013). One study also found subcortical activity in the putamen during the grouped interpretation (Zaretskaya et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…Previous studies repeatedly showed increased activity in parts of the parietal cortex (especially IPS and supramarginal gyrus) and a decrease in early visual areas (V1, V2) when participants perceived ambiguous stimuli as a grouped illusory Gestalt rather than an array of single elements (Carther-Krone et al, 2020;De-Wit et al, 2012;Fang et al, 2008;Grassi et al, 2016;Murray et al, 2002;Zaretskaya et al, 2013). One study also found subcortical activity in the putamen during the grouped interpretation (Zaretskaya et al, 2013).…”
Section: Introductionmentioning
confidence: 93%
“…In humans, the contour illusions are predominantly processed in the cortical areas confined to the visual cortex, mainly in V1 and V2 (Ffytche and Zeki 1996 ; Seghier and Vuilleumier 2006 ). Conversely, the perception of distortion illusions requires also an integration of higher cortical areas responsible for numerical skills and magnitude estimation (Axelrod et al 2017 ; Carther-Krone et al 2020 ; Qiu et al 2008 ; Weidner and Fink 2007 ). To date, it is unknown where exactly the visual illusions are processed in the canine brain.…”
Section: Discussionmentioning
confidence: 99%
“…Given its role in the dorsal attention network, it is plausible that IPS is more central to intentionally attending to the global form, rather than actually constructing the global perception itself (Weissman & Woldorff, 2005). In contrast, a study using Ponzo illusion stimuli (see Figure 6d) suggests the TPJ is central to integrating the local elements into a global percept even in the absence of attention (Carther-Krone et al, 2020). This finding speaks to the effortlessness of TPJ's contribution.…”
Section: Proposition 1: Ceeing Occurs In Gestalt Cortexmentioning
confidence: 93%
“…First, global perception activates gestalt cortex Carther-Krone et al, 2020;Himmelbach et al, 2009), but global perception also suppresses activity in early visual areas (e.g. V1/V2) associated with the local aspects of perception (Grassi, Zaretskaya, & Bartels, 2017).…”
Section: Proposition 4: Ceeing Leads To Inhibition Of Alternative Construals (Or Their Underlying Elements)mentioning
confidence: 99%